IMPACT OF DIGITAL MARKETING ON THE PERFORMANCE OF COMPANIES IN THE AGRICULTURAL SECTOR OF SERBIA - Branko Miodrag Mihailović; Katica Radosavljević; Vesna Popović; Anton Puškarić (Ekonomika Poljoprivrede (1979), 2024)
This paper explores the impact of digital marketing on the business operations of companies in the agricultural sector of Serbia. Accordingly, the research objective is to determine critical success factors of digital marketing channels in companies within this sector. Given the stated research objective, the following general hypothesis has been formulated: digital marketing channels such as effective presence on social media, website quality, online sales and search engine optimization have a significant positive impact on the business performance of companies in the agricultural sector in Serbia. Successful implementation of these types of digital marketing channels by companies is expected to lead to increased visibility, engagement of the target audience, and improved sales. Consequently, the results of empirical research provide more insightful perspectives on the state of this field, identifying specific aspects of digital marketing that significantly contribute to the business performance of companies in the agricultural sector of Serbia.